Terapi Non Farmakologi Terhadap Mual Muntah dan Hiperemesis Gravidarum Pada Ibu Hamil: a Literatur Review - Diana, Sirlii; Sumarni, Sumarni (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The incidence of nausea and vomiting affects almost 50% to 80% of pregnant women and approximately 5% of pregnant women require treatment in the form of hospitalisation for fluid replacement and correction of electrolyte imbalances. Non-pharmacological therapy is needed as an alternative or complementary treatment if pharmacological therapy causes side effects. in some cases nausea, vomiting, and hyperemesis gravidarum. This literature review aims to identify non-pharmacological therapies to help mothers overcome nausea, vomiting, and hyperemesis gravidarum in pregnancy. Five electronic databases were used for literature review research: PubMed, ProQuest, Google Scholar, Wiley Online Library, and Science Direct between 2014 and 2024. Of the 3,070 articles, 12 articles met the inclusion criteria and were analysed. This literature review provides evidence of non-pharmacological therapy methods that can be used as an alternative to treat nausea, vomiting, and hyperemesis gravidarum in pregnant women, namely oral therapy (ginger, mint leaves, and dates), inhalation therapy (lemon aromatherapy, lavender aromatherapy, and ginger aromatherapy) and therapy through massage (P6 acupressure and ST36 acupressure). The most frequently used and effective therapeutic methods for treating nausea, vomiting, and hyperemesis gravidarum in pregnant women are ginger therapy, lemon aromatherapy, and P6 acupressure.